2020
DOI: 10.1097/mnm.0000000000001191
|View full text |Cite
|
Sign up to set email alerts
|

Simplified dual time point FDG-PET/computed tomography for determining dignity of pancreatic lesions

Abstract: Background Predicting the dignity of pancreatic lesions is still a diagnostic challenge. The differentiation between benign changes in chronic pancreatitis from pancreatic cancer remains difficult. Therefore, the aim of this study was to evaluate whether early dual time point kinetics of pancreatic lesions in 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) may be helpful to differentiate pancreatic lesions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…32 Several previous studies reported controversial and conflicting results of DTP 18 F-FDG PET/CT in various cancer type for differentiation of malignant from benign lesions. [8][9][10][33][34][35][36][37][38] In HCC patients, Oksuzoglu et al 33 showed that a significant increase in tumor SUV in delayed images in contrast to a significant decrease in background SUVs suggests that delayed images in HCC may contribute to diagnostic performance through a potential increase in the contrast between the tumor and background. According to studies performed in breast cancer patients, Yamagishi et al 34 showed that DTP 18 F-FDG PET/CT can be a useful method for predicting relapse in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Several previous studies reported controversial and conflicting results of DTP 18 F-FDG PET/CT in various cancer type for differentiation of malignant from benign lesions. [8][9][10][33][34][35][36][37][38] In HCC patients, Oksuzoglu et al 33 showed that a significant increase in tumor SUV in delayed images in contrast to a significant decrease in background SUVs suggests that delayed images in HCC may contribute to diagnostic performance through a potential increase in the contrast between the tumor and background. According to studies performed in breast cancer patients, Yamagishi et al 34 showed that DTP 18 F-FDG PET/CT can be a useful method for predicting relapse in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, to better differentiation of benign from malignant conditions, many studies have found interesting results using dual-timepoint (DTP) acquisition of 18 F-FDG PET and PET/CT for various malignant diseases. [7][8][9][10][11] Few recent studies reported that retention index (RI) or % change of maximal standardized uptake values (%ΔSUV max ) calculated from early and delayed 18 F-FDG PET/CT provide a significantly more accurate diagnosis in lung cancer than does early 18 F-FDG PET or PET/CT and chest CT and that a close correlation exists between the RI and SUV results for the primary lesion and LN metastases. 12,13 Although this newly described DTP imaging of 18 F-FDG PET seems to be an effective method for distinguishing benign from malignant lesions, fewer studies has attempted to adopt this technique for the evaluation of mediastinal LN node status in patients with NSCLC with controversial results.…”
mentioning
confidence: 99%
“…In many PET studies, standardized uptake (SUV) value of FDG at the time of FDG-PET imaging is quantitatively analyzed and displayed. In addition, SUV uptake change over time is analyzed over 30-60 min using DTPI in various oncology fields [33][34][35][36][37][38][39][40]. On the basis of the concept of differences in glucose metabolism, FDG uptake tends to increase or remain high in many malignant lesions as compared to benign lesions including infection and inflammation.…”
Section: Potential Roles For Quantitative Assessmentmentioning
confidence: 99%
“…Recent studies have used dual-time-point 18 F-FDG PET/CT to better diagnostic or prognostic accuracy for various malignant disease, because of the more prominent 18 F-FDG uptake in malignant conditions, whereas with less 18 F-FDG uptake in benign or non-tumorous conditions on a delayed scan [8–13] . But few studies have applied this technique for assessment of malignant potential in patients with extrahepatic bile duct cancer or biliary strictures [14–16] .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Recent studies have used dual-time-point 18 F-FDG PET/CT to better diagnostic or prognostic accuracy for various malignant disease, because of the more prominent 18 F-FDG uptake in malignant conditions, whereas with less 18 F-FDG uptake in benign or non-tumorous conditions on a delayed scan. [8][9][10][11][12][13] But few studies have applied this technique for assessment of malignant potential in patients with extrahepatic bile duct cancer or biliary strictures. [14][15][16] Because dual-time-point imaging technique has been known to overcome partial volume effect and to emerge as prominent small lesion, this technique might be helpful to bile duct cancers with small and narrow structure.…”
Section: Introductionmentioning
confidence: 99%